2015
DOI: 10.1103/physreve.91.032305
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb energy of uniformly charged spheroidal shell systems

Abstract: We provide exact expressions for the electrostatic energy of uniformly-charged prolate and oblate spheroidal shells. We find that uniformly-charged prolate spheroids of eccentricity greater than 0.9 have lower Coulomb energy than a sphere of the same area. For the volume-constrained case, we find that a sphere has the highest Coulomb energy among all spheroidal shells. Further, we derive the change in the Coulomb energy of a uniformly-charged shell due to small, area-conserving perturbations on the spherical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…By virtue of the electrostatics-driven deformation, environmental (solutionbased) control strategies (e.g., tuning salt concentration) as well as materials design approaches (e.g., tuning surface charge) were demonstrated as a feasible means of controlling container shape and changing preferences for bowl-like or disc-like morphologies. Effects of ion condensation were analyzed using a two-state Manning mean-field model, which supported the feasibility of the observed shape transitions 39,44 .…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…By virtue of the electrostatics-driven deformation, environmental (solutionbased) control strategies (e.g., tuning salt concentration) as well as materials design approaches (e.g., tuning surface charge) were demonstrated as a feasible means of controlling container shape and changing preferences for bowl-like or disc-like morphologies. Effects of ion condensation were analyzed using a two-state Manning mean-field model, which supported the feasibility of the observed shape transitions 39,44 .…”
Section: Introductionmentioning
confidence: 66%
“…Early work on charged elastic membranes (shells) mainly focused on mapping a charged, deformable membrane to an uncharged, deformable membrane with charge-renormalized elastic parameters [40][41][42] . Recent studies have modeled Coulomb interactions explicitly to accurately describe the nonlinear coupling between elastic and electrostatic forces in charged nanoscale containers where the surface charge density can assume high values ( 0.1e/ nm 2 ) 38,43,44 . Using such models, it has been shown that an ionic shell, where positive and negative charges populate the surface, lowers its energy by taking a faceted (icosahedral) shape with the same surface area 43 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, there have not been corresponding developments towards a general methodology for treating electrostatic interactions between non-spherical particles. Exact solutions to this problem have only been presented for a single uniformly charged spheroidal shell, 30 and where the image charge method has been used to treat conducting ellipsoidal particles. 31 In this paper, an analytical theory of electrostatic interactions between spheroidal particles has been developed, building on previous work, [32][33][34][35][36] where analytical expressions have been given for the electrostatic force between charged, dielectric sphere -sphere 32 and sphereplanar surface systems.…”
Section: Introductionmentioning
confidence: 99%
“…For nonspherical shapes, the screened-electrostatic pair interaction is only analytically known in a few cases for all particle configurations, even within linear screening theory. However, some studies exist for disks [35][36][37][38], rods [39,40], spheroids [41][42][43][44][45], or helices [46], where the potential is sometimes calculated only for infinitely long, thin, or ion-penetrable particles, restricted particle configurations, or orientation-averaged interactions [47]. The difficulty in finding analytical solutions lies in the finite ion-impenetrable particle volume which complicates matching the series expansion solution (if it is even available for the geometry under consideration) of the unscreened potential inside and the screened potential outside the particle via the boundary conditions.…”
Section: Introductionmentioning
confidence: 99%